The effect of glycation on oil–water emulsion properties of β-lactoglobulin - Medrano, Alejandra (2012)
The creaming, flocculation and coalescence processes of destabilization of emulsions prepared with glycated β-lactoglobulin was analyzed. The glycation process was carried out with glucose and lactose in different reaction conditions (reaction time and protein:carbohydrate molar ratio) The glycation of β-lactoglobulin with both with glucose and lactose causes an increase in the stability of oil–water emulsions. It was found that the process of creaming had a sigmoid behavior which fit to an equation with two parameters, one with hyperbolic and other with sigmoidal kinetics and is directly related to particle size of the dispersed phase of the emulsion. β-lactoglobulin glycated with lactose emulsions showed greater stability to creaming than those prepared with β-lactoglobulin glycated with glucose, which was related to the decrease in the particle size of the dispersed phase and the increased concentration of protein at the interface of the emulsions. Flocculation and coalescence were not influenced by the glycation. Highlights: ► Glycated β-lactoglubulin emulsions were more stable to creaming. ► Unfolding of β-lactoglubulin was greater with the increase of the carbohydrate size. ► The increase of the carbohydrate size attached produced more resistant films. ► The processes of flocculation and coalescence were not affected by glycation.